AUTORADIOGRAPHIC EVIDENCE FOR MANY SEGREGATING DNA MOLECULES IN THE CHLOROPLAST OF OCHROMONAS DANICA - Gibbs, Sarah P. (The Rockefeller University Press, 1973)

(untitled)
Light-grown cells of Ochromonas danica, which contain a single chloroplast per cell, were labeled with [methyl-(3)H]thymidine for 3 h (0.36 generations) and the distribution of labeled DNA among the progeny chloroplasts was followed during exponential growth in unlabeled medium for a further 3.3 generations using light microscope autoradiography of serial sections of entire chloroplasts. Thymidine was specifically incorporated into DNA in both nuclei and chloroplasts. Essentially all the chloroplasts incorporated label in the 3-h labeling period, indicating that chloroplast DNA is synthesized throughout the cell cycle. Nuclear DNA has a more limited S period. Both chloroplast DNA and nuclear DNA are conserved during 3.3 generations. After 3.3 generations in unlabeled medium, grains per chloroplast followed a Poisson distribution indicating essentially equal labeling of all progeny chloroplasts. It is concluded that the average chloroplast in cells of Ochromonas growing exponentially in the light contains at least 10 segregating DNA molecules.